2021
DOI: 10.1002/ehf2.13267
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score‐based analysis of long‐term outcome of patients on HeartWare and HeartMate 3 left ventricular assist device support

Abstract: Aims Left ventricular assist device therapy has become the cornerstone in the treatment of end-stage heart failure and is increasingly used as destination therapy next to bridge to transplant or recovery. HeartMate 3 (HM3) and HeartWare (HVAD) are centrifugal continuous flow devices implanted intrapericardially and most commonly used worldwide. No randomized controlled trials have been performed yet. Analysis based on large registries may be considered as the best alternative but has the disadvantage of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 19 publications
6
41
2
Order By: Relevance
“…Although it did not reach a statistical level of significance, a trend toward lower daily beta blocker doses were observed in patients with the HM3 compared to those with the HVAD device (3.75 mg vs. 5 mg; p = 0.085). We hypothesized that the results of previous clinical trials demonstrating the superiority of the HM3 device with respect to thromboembolic events [ 11 , 12 , 13 , 14 ] may have led to differences in the stringency of blood pressure management and thus lower doses of beta blockers in patients implanted with the HM3. Thus, our results suggest that it is not the device design per se, but differences in best practices in patient care that lead to a lower incidence of RHF in patients with the HM3 device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it did not reach a statistical level of significance, a trend toward lower daily beta blocker doses were observed in patients with the HM3 compared to those with the HVAD device (3.75 mg vs. 5 mg; p = 0.085). We hypothesized that the results of previous clinical trials demonstrating the superiority of the HM3 device with respect to thromboembolic events [ 11 , 12 , 13 , 14 ] may have led to differences in the stringency of blood pressure management and thus lower doses of beta blockers in patients implanted with the HM3. Thus, our results suggest that it is not the device design per se, but differences in best practices in patient care that lead to a lower incidence of RHF in patients with the HM3 device.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a less invasive surgical implantation strategy has been suggested to have a protective effect on the development of RHF after LVAD implantation [ 10 ]. Recent studies have suggested the superiority of the HeartMate 3 (HM3) (Abbott Inc., Chicago, IL, USA) over the HVAD (Medtronic Inc., Minneapolis, MN, USA) device in terms of the occurrence of thromboembolic events [ 11 , 12 , 13 , 14 ]; however, other analyses have failed to identify substantial differences [ 15 ]. A possible superiority of the HM3 vs. HVAD device in terms of the development of RHF has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, all of those patients suffered from progressive heart failure or ongoing cardiogenic shock and were classified as INTERMACS class I or II. Furthermore, a high proportion of HVAD implantations within the current analysis might have negatively influenced long-term survival, as there is growing evidence of a higher frequency of neurological adverse events and mortality among HVAD recipients as compared to other commercially available durable LVADs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no prospective, comparative clinical trials of HVAD and HeartMate 3, there is a growing body of evidence that clinicians favor the more recently introduced device. Numan and colleagues 13 analyzed a propensitymatched cohort of patients with Heartmate 3 and HVAD and found no difference in survival but greater rates of pump thrombosis and hemorrhagic stroke with HVAD. Analyses of the Intermacs (Interagency Registry for Mechanically Assisted Circulatory Support) registry using propensity-matched populations implanted between 2017 and 2019 have also recently demonstrated that HVAD is associated with a 5-to 6-fold increase in stroke and a 3.2fold increase in mortality relative to HeartMate 3.…”
Section: Central Messagementioning
confidence: 99%